Allopurinol effects on residual renal function in end-stage renal disease patients undergoing peritoneal dialysis: Randomized controlled trial - Firouzeh Moeinzadeh; Elham Kabiri Naeini; Mojgan Mortazavi (Journal of Research in Pharmacy Practice, 2019)
Objective: There is increasing evidence to show that hyperuricemia may have a pathogenic role in the progression of renal diseases. We performed a prospective, randomized, controlled trial to investigate the renal effects of allopurinol treatment in hyperuricemic patients with end-stage renal disease (ESRD) who undergo peritoneal dialysis. Methods: This was a unicenter, randomized, controlled clinical trial conducted in “Alzahra Hospital, Isfahan, Iran.” Patients were randomly assigned into treatment or control group. Treatment-group patients were administered a starting allopurinol dose of 100 mg/day. The dose was adjusted according to serum uric acid level, aiming to maintain uric acid levels within the normal range. Participants were followed up for 6 months after receiving the medicine. Residual renal function (RRF) was assessed by measuring the renal component of Kt/V urea and estimating the patient's glomerular filtration rate (GFR) by calculating the mean of urea and creatinine clearance. In addition, systolic and diastolic blood pressure and serum level of creatinine were measured every 3 months during the follow-up period. Findings: Eighty patients were enrolled in the study and divided into two groups, including 40 ESRD patients receiving allopurinol and 40 ESRD did not receive allopurinol and considered as the control group. GFR measurements showed that there was not a significant difference between patients' RRF of two groups. However, allopurinol group had higher RRF than the control group during the follow-up period. Evaluating RRF by Kt/V showed the same results. Conclusion: Our study demonstrated significant effects of allopurinol on decreasing serum levels of uric acid in ESRD patients undergoing peritoneal dialysis. On the other hand, renal residual function of patients under treatment with allopurinol was better than the control group. We recommend that further studies should be conducted on the effects of allopurinol with greater sample size and longer time of follow-up.